Endothelial Dysfunction, Increased Arterial Stiffness, and Cardiovascular Risk Prediction in Patients With Coronary Artery Disease: FMD‐J (Flow‐Mediated Dilation Japan) Study A. Issue 14 (17th July 2018) - Maruhashi, Tatsuya; Soga, Junko; Fujimura, Noritaka; Idei, Naomi; Mikami, Shinsuke; Iwamoto, Yumiko; Iwamoto, Akimichi; Kajikawa, Masato; Matsumoto, Takeshi; Oda, Nozomu; Kishimoto, Shinji; Matsui, Shogo; et al.
Abstract : Background: The usefulness of vascular function tests for management of patients with a history of coronary artery disease is not fully known. Methods and Results: We measured flow‐mediated vasodilation (FMD) and brachial–ankle pulse wave velocity (baPWV) in 462 patients with coronary artery disease for assessment of the predictive value of FMD and baPWV for future cardiovascular events in a prospective multicenter observational study. The first primary outcome was coronary events, and the second primary outcome was a composite of coronary events, stroke, heart failure, and sudden death. During a median follow‐up period of 49.2 months, the first primary outcome occurred in 56 patients and the second primary outcome occurred in 66 patients. FMD above the cutoff value of 7.1%, derived from receiver‐operator curve analyses for the first and second primary outcomes, was significantly associated with lower risk of the first (hazard ratio, 0.27; 95% confidence interval, 0.06–0.74; P =0.008) and second (hazard ratio, 0.32; 95% confidence interval, 0.09–0.79; P =0.01) primary outcomes. baPWV above the cutoff value of 1731 cm/s was significantly associated with higher risk of the first (hazard ratio, 1.86; 95% confidence interval, 1.01–3.44; P =0.04) and second (hazard ratio, 2.19; 95% confidence interval, 1.23–3.90; P =0.008) primary outcomes. Among 4 groups stratified according to the combination of cutoff values of FMD and baPWV, stepwise increases in the calculated risk ratio for the first and second primary outcomes were observed. Conclusions: In patients with coronary artery disease, both FMD and baPWV were significant predictors of cardiovascular events. The combination of FMD and baPWV provided further cardiovascular risk stratification. Clinical Trial Registration: URL: www.umin.ac.jp . Unique identifier: UMIN000012950.